2011
DOI: 10.1007/s11357-011-9357-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in human and non-human primate white matter: from myelination disturbances to cognitive decline

Abstract: The cognitive decline associated with normal aging was long believed to be due primarily to decreased synaptic density and neuron loss. Recent studies in both humans and non-human primates have challenged this idea, pointing instead to disturbances in white matter (WM) including myelin damage. Here, we review both cross-sectional and longitudinal studies in humans and non-human primates that collectively support the hypothesis that WM disturbances increase with age starting at middle age in humans, that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 175 publications
3
97
0
1
Order By: Relevance
“…The decreased expression was due, at least in part, via the hypermethylation of the KL promoter (King et al 2012a). Decreased levels of KL correlate with ubiquitous dysmyelination observed in the brains of aged monkeys by us as well as by other groups (Sloane et al 2003;Hinman et al 2006;Hinman and Abraham 2007;Makris et al 2007;Wisco et al 2008;Bowley et al 2010;Kohama et al 2012). In support of a possible involvement of KL in myelination of the CNS, we have reported that KL-KO mice exhibited severely impaired myelination of the optic nerve and corpus callosum accompanied by significant abnormalities at the nodes of Ranvier.…”
Section: Introductionsupporting
confidence: 57%
“…The decreased expression was due, at least in part, via the hypermethylation of the KL promoter (King et al 2012a). Decreased levels of KL correlate with ubiquitous dysmyelination observed in the brains of aged monkeys by us as well as by other groups (Sloane et al 2003;Hinman et al 2006;Hinman and Abraham 2007;Makris et al 2007;Wisco et al 2008;Bowley et al 2010;Kohama et al 2012). In support of a possible involvement of KL in myelination of the CNS, we have reported that KL-KO mice exhibited severely impaired myelination of the optic nerve and corpus callosum accompanied by significant abnormalities at the nodes of Ranvier.…”
Section: Introductionsupporting
confidence: 57%
“…Studies of the effects of age on microglia have reported that microglial activation increases with age (Henry et al 2009). It has also been noted that activation occurs primarily in white matter rather than gray matter (Hart et al 2012) and, in the monkey, is associated with cognitive impairment (Sloane et al 1999; for review, see Kohama et al 2011;Peters and Kemper 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if proBDNF is the intermediate protein, the reduced proBDNF would be a result of the neuron compensating to preserve mBDNF levels and signaling to preserve the cell and synapse. However, the decreased action potential conduction due to myelin damage would decrease the ability of the mBDNF to act on the synapse leading to the loss of the spines and axon (Kohama et al 2012).…”
Section: Bdnf and Normal Agingmentioning
confidence: 99%
“…This in turn could decrease trophic factor feedback. Since BDNF supports the axon (for review see (Poo 2001)), decreased trophic feedback from the postsynaptic cell to the axon could cause the retraction of the axon and the axonal loss visible in the white matter as discussed by Kohama et al 2012. The decreased trophic feedback could also be reflected in reported decreases in the number of dendritic spines and synapses on the postsynaptic cells (Dickstein et al 2013).…”
Section: Sex Differences In Bdnf Expressionmentioning
confidence: 99%